Intravenous Ceftriaxone Versus Multiple Dosing Regimes of Intravenous Anti-Staphylococcal Antibiotics for Methicillin-Susceptible Staphylococcus aureus (MSSA): A Systematic Review - Musaiwale M. Kamfose; Francis G. Muriithi; Thomas Knight; Daniel Lasserson; Gail Hayward (Antibiotics, 2020)
Background: Methicillin-susceptible Staphylococcus aureus (MSSA) is a common pathogen associated with a range of clinically important infections. MSSA can cause deep-seated infections requiring prolonged courses of intravenous antibiotic therapy to achieve effective resolution. The move toward ambulatory or outpatient delivery of parenteral antibiotics has led to an increase in the use of ceftriaxone as a pragmatic first choice given its advantageous single daily dosing schedule. Objective: To compare the efficacy of once daily ceftriaxone in the treatment of infections due to confirmed or suspected MSSA to multiple dosing regimes of anti-staphylococcal antibiotics. Methods: We searched the Cochrane Central Register of Controlled Trials (CENTRAL), Database of Abstracts of Reviews of Effects (DARE), Global Health, PubMed, EMBASE and CINAHL for randomised controlled trials as well as prospective and retrospective cohort studies that compared ceftriaxone to any multiple dosing regime of anti-staphylococcal antibiotics. Outcome measures were the proportion of patients with a resolution of infection based on time after initiation of therapy, adverse reactions, recurrence and duration of hospital admission. Results: We included two randomized controlled trials, one prospective observational study and three retrospective cohort studies (643 participants; 246 children, 397 adults). There was no difference in time to resolution of symptoms. The number of adverse reactions, recurrence of bacteraemia and duration of hospital stay were not significantly different between ceftriaxone and other anti-staphylococcal antibiotics. Conclusions: Based on a small number of low-quality studies, ceftriaxone is as effective as multiple dosing regimes for the treatment of infections due MSSA. An appropriately powered randomized trial is required to demonstrate equivalence and cost effectiveness.